Давньогрецькі монети на Кіровоградщині - Саросіян, Є.; Sarosiyan, E. (ЦНТУ, 2025)
У статті проаналізовано знахідки давньогрецьких монет на території Кіровоградщини, зокрема емісії Ольвії, Пантікапея, Гермонасса та монети Боспорської держави, що датуються VI–I ст. до н. е. Встановлено, що їх поширення у басейні р. Тясмин та на прилеглих територіях свідчить про активні торговельно-економічні контакти місцевого населення з античними центрами Північного Причорномор’я. The article analyzes the finds of ancient Greek coins in the Kirovohrad region, in particular, the issues of Olbia, Panticapaeum, Hermonassa and coins of the Bosporus state, dating from the 6th–1st centuries BC. It was established that their distribution in the basin of the Tyasmin River and in the adjacent territories indicates active trade and economic contacts of the local population with the ancient centers of the Northern Black Sea region.
Ancient Greek coins in the Kirovohrad region
Keywords: давньогрецькі монети; Кіровоградщина; античні торговельні зв’язки; нумізматичні знахідки; ancient Greek coins; Kirovograd region; ancient trade relations; numismatic finds